OFICINAS TERAPÊUTICAS DE CONTOS - Drugg, Angela M. S.; Schonardie, Elisiane; Nogara, Gabriela; Padilha, Alessandra S.; Serafim, Rodrigo G.; Schalemberg, Ana P.; Ficher, Flávia V.; Severo, Mirela M. (Salão do Conhecimento, 2013)
Resumo